Implementation of Inquiry Method in Science Subject to Improve Learning Outcomes of Second Grade Elementary School Students - Rahmawati, Ery; Nanda Faradita, Meirza (Universitas Nusantara PGRI Kediri, 2024)
Natural and Social Sciences (IPAS) should be a vehicle for students to study the natural surroundings and then apply it in everyday life so that students' learning experiences are meaningful. However, in reality, IPAS learning at UPT SD Negeri 144 Gresik is still teacher-centered and does not involve students in the teaching and learning process so that students do not understand the material, so that student learning outcomes are low. Based on the background of the problem, the researcher uses the inquiry learning method to improve student learning outcomes. The purpose of this study is an effort to improve the learning outcomes of grade II elementary school students in the subject of IPAS on energy sources. The subjects of this study were students in grade II of UPT SD Negeri 144 Gresik. The research method uses Classroom Action Research (CAR), with a CAR cycle model consisting of planning, implementing actions, observing, and reflecting. From the test results that have been conducted, the following data were obtained: The learning completion of class II students of UPT SD Negeri 144 Gresik increased by 47.56% from 40.9% (pre-cycle) to 88.46% (cycle II), and the average student learning outcomes increased by 24.23% from 58.84 (pre-cycle) to 83.07 (cycle II) after using the inquiry method. Based on the test results obtained during the study, it can be concluded that the inquiry method can improve the learning outcomes of class II students at UPT SD Negeri 144 Gresik.